Pengaruh Latihan Interval terhadap Peningkatan Daya Tahan Kardiovaskular Atlet Muda - Nayla Prameswari; Aulia Kirana Permata (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study evaluated the effect of interval training on improving cardiovascular endurance in young athletes. A total of 30 athletes aged 15-18 years participated in an interval training program for 8 weeks. The results showed a significant increase in aerobic capacity and cardiac efficiency compared to the control group that underwent conventional exercise. This study recommends interval training as an effective strategy in improving the physical endurance of young athletes.